2015
DOI: 10.1016/j.porgcoat.2014.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Toward halogen-free flame resistant polyethylene extrusion coated paper facings

Abstract: Wire and cable coverings are potentially a major cause of fire in buildings and other installations. As they need to breach fire walls and are frequently located in vertical ducting, they have significant potential to increase the fire hazard. It is therefore important to understand the ignition and burning characteristics of cables by developing a model capable of predicting their burning behaviour for a range of scenarios. The fire performance of electrical cables is usually dominated by the fire performance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…Brominated FRs act as flame inhibitors in gaseous phase. Recent works have shown that other classes of FR can act as flame inhibitor, namely azoalkanes and derivatives (Aubert et al, 2011a(Aubert et al, , b, 2012Pawelec et al, 2012Pawelec et al, , 2015Tirri et al, 2014), disulfides (Pawelec et al, 2014) and sulfenamides (Tirri et al, 2016). They were found to be effective at very low content (typically 0.5 wt%) especially for polyolefins and polystyrene, alone or in synergy with various FRs (brominated FR, alumina trihydrate).…”
Section: Fr-pmentioning
confidence: 99%
“…Brominated FRs act as flame inhibitors in gaseous phase. Recent works have shown that other classes of FR can act as flame inhibitor, namely azoalkanes and derivatives (Aubert et al, 2011a(Aubert et al, , b, 2012Pawelec et al, 2012Pawelec et al, , 2015Tirri et al, 2014), disulfides (Pawelec et al, 2014) and sulfenamides (Tirri et al, 2016). They were found to be effective at very low content (typically 0.5 wt%) especially for polyolefins and polystyrene, alone or in synergy with various FRs (brominated FR, alumina trihydrate).…”
Section: Fr-pmentioning
confidence: 99%
“…In addition to structural engineering employment, polyethylene is widely employed in packaging applications [ 58 , 59 ]. Specifically, LDPE is often used to coat paper as a moisture barrier [ 60 , 61 ]. To this end, we compared the water barrier properties of natural kraft paper covered with LDPE and the paper impregnated with CW and covered with PBBM-X/CW (40%).…”
Section: Resultsmentioning
confidence: 99%
“…Wileń and colleagues have synthesized a series of azo-based FRs such as azos (R−NN−R) and/or triazenes (R−NN−N−R), which achieved excellent fire retardancy in a PP system 33,34 and a PE system. 35 Additionally, incorporation of azobenzene groups in a copolyester can significantly increase the amount of residue and thermo-oxidative stability due to its high-temperature self-cross-linking characteristics. 36 Moreover, the azo compounds possess good UV absorption ability.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Recently, some articles reported that when LDHs were modified by organic anions such as SDBS, DBS, SPDP, CEPPA, and SIEPDP, they greatly increased the interlayer distance and thus enhanced the dispersion properties and the fire-retardant properties of the composites. Wilén and colleagues have synthesized a series of azo-based FRs such as azos (R–NN–R) and/or triazenes (R–NN–N–R), which achieved excellent fire retardancy in a PP system , and a PE system . Additionally, incorporation of azobenzene groups in a copolyester can significantly increase the amount of residue and thermo-oxidative stability due to its high-temperature self-cross-linking characteristics .…”
Section: Introductionmentioning
confidence: 99%